Efficient down-regulation of glia maturation factor expression in mouse brain and spinal cord - Zaheer, Smita (2012)
Long-lasting siRNA-based down-regulation of gene of interest can be achieved by lentiviral-based expression vectors driving the production of short hairpin RNA (shRNA). We investigated an attractive therapeutic approach to target the expression of proinflammatory GMF by using lentiviral vector encoding GMF-specific shRNA to reduce GMF levels in the spinal cord and brain of mice. To determine the effect of GMF-shRNA on GMF protein levels, we performed quantitative ELISA analysis in brain and in thoracic, cervical and lumbar regions of spinal cord from mice followed by GMF-shRNA (G-shRNA) or control shRNA (C-shRNA) treatments. Our results show a marked reduction of GMF protein levels in brain and spinal cord of mice treated with GMF-shRNA compared to control shRNA treatment. Consistent with the GMF protein analysis, the immunohistochemical examination of the spinal cord sections of EAE mice treated with GMF-shRNA showed significantly reduced GMF-immunoreactivity. Thus, the down-regulation of GMF by GMF-shRNA was efficient and wide spread in CNS as evident by the significantly reduced levels of GMF protein in the brain and spinal cord of mice.